2018
DOI: 10.18203/2349-3933.ijam20180071
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of PCR for MTB in comparison to ADA in diagnosing tubercular pleural effusion

Abstract: Background: Tuberculosis continues to be an important health problem globally. The bacteriological confirmation of diagnosis in extrapulmonary tuberculosis patients is more difficult because most of the cases of extrapulmonary tuberculosis are paucibacillary in nature. In this study we have compared the pleural fluid ADA levels with PCR for MTB in pleural fluid to confirm the diagnosis of tuberculosis in the pleural fluid.Methods: The study was done over two years and a total of 106 patients with a clinico-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similar observation has been made in an Indian study done on 106 subjects. They found that in patients with pleural effusion with underlying lung consolidation, the overall sensitivity of PCR for MTB was 92.8% for diagnosing TB pleural effusion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observation has been made in an Indian study done on 106 subjects. They found that in patients with pleural effusion with underlying lung consolidation, the overall sensitivity of PCR for MTB was 92.8% for diagnosing TB pleural effusion [11].…”
Section: Discussionmentioning
confidence: 99%